Efeito da própolis e de estratos obtidos de Baccharis dracunculifolia sobre a replicação do poliovírus tipo 1 em células HEp-2 - Búfalo, Michelle Cristiane [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Baccharis dracunculifolia is the most important vegetal source of propolis in southeast Brazil, and researchers have been investigating its biological properties. Propolis is a complex resinous hive product collected by bees from several plants, showing a very complex chemical composition. It has been employed since ancient times, due to its therapeutic properties, such as antimicrobial, antiinflammatory, antioxidant, immunomodulatory and antitumoral activities, among others. The goal of this work was to compare the cytotoxic action of B. dracunculifolia, propolis and 2 isolated compounds (caffeic and cinnamic acids) on HEp-2 cells in vitro. These cells were incubated with different concentrations of each variable, and cell viability was assessed by crystal violet method. Lower concentrations of B. dracunculifolia (extract and essential oil), propolis as well as caffeic and cinnamic acids, showed no cytotoxic activity against HEp-2 cells. On the other hand, elevated concentrations (50 and 100 μg/100μL) exerted a cytotoxic action, and propolis showed a more efficient action than its vegetal source and isolated compounds. Further investigation is still needed in order to explore the potential of these variables as antitumor agents and to understand their mechanisms of action. Baccharis dracunculifolia is the most important botanical source of the southeastern Brazilian propolis, and its potential for the development of new phytotherapeutic medicines has been investigated. Propolis is commonly used for its antimicrobial and immunomodulatory activities. Nevertheless, B. dracunculifolia and propolis effects on poliovirus type 1 (PV1) were not investigated yet. Thus, the aim of this work was to evaluate the antiviral activities of B. dracunculifolia (extract and essential oil), propolis and some isolated compounds (caffeic and cinnamic acids) against PV1 replication in HEp-2 cells in three... (Complete abstract click electronic access below)
Keywords: Matéria médica vegetal; Própole - Efeitos fisiológicos; Polivírus - Tratamento; Própole; Baccharis dracunculifolia; Propolis